PELAKSANAAN PROGRAM PENGEMBANGAN PERUMAHAN MELALUI SKEMA FASILITAS LIKUIDITAS PEMBIAYAAN PERUMAHAN (FLPP) PADA KANTOR BANK RAKYAT INDONESIA (BRI) SYARIAH CABANG PALEMBANG - Dewiwati, Eva (Jurnal Governance dan Administrasi Publik, 2020)
The purpose of this study is to investigate the implementation of the program through a scheme FLPP residential development and the factors supporting and inhibiting the program. The data used in this study is primary data and secondary data. Primary data compiled from the observations and interviews with BRI Syariah Branch Manager, employees, customers and developers. While the secondary data obtained from the study of literature, documentation and BRI Syariah Cabang Palembang. The results of this study indicate that the new BRI Syariah FLPP implement the program in 2012 and until now has 77 houses were built, meaning not reached the set target. The factors supporting this program include human resources professional, readiness bank executive, developer of reliable, customers who pay the mortgage on time, and the support of the institution where the customer works. While inhibiting factors include the price of land and construction materials are expensive, inadequate income customers as well as the constraints that can be financed with FLPP. To implement the program Syariah BRI has set its human resources by providing education and training. So far the program is going well despite not reaching their intended target because there are many factors inhibiting the implementation of the program. In order to minimize these inhibiting factors so Kemenpera need to lower margin of 6%, in setting prices Kemenpera should pay attention to the conditions of each region, the intense socialization to the community and constructing facilities and infrastructure are adequate.